Risk Factor Analysis in Community with Consuming Habits Caffeinated Drinks - Lingga Kusuma Wardani; Febriana Ina Lemba; Joel Rey Ugsang Acob (Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Background: People in general have a habit of consuming coffee every day, from various social status circles they like coffee drinks with different consumption goals. Caffeine is widely found in beverages, drugs, supplements and sweets, is the most widely used stimulant in the world, caffeine is a central nervous system stimulant, diuretic, stimulates the heart muscle, and relaxes bronchial smooth muscles. At standard doses, 50-200 mg of caffeine primarily affects the outer layer of the brain. This effect can reduce fatigue, however the caffeine consumed also turns out to have side effects. Purpose: The purpose of this study is to analyze the risk factors in the community with the habit of consuming caffeinated drinks. Methods: The design used is a literature review by using several journals from several sources such as: Google Scholar, The keyword used to conduct the search is "factors that influence people's behavior in consuming caffeine drinks", the year of publication are 2015-2020. Results: The results of the journal discussion showed that the risk factors in the community with the habit of consuming caffeinated beverages had an effect on the health of the individual itself because the dangers of coffee could arise if excessive coffee consumption, which caused the heart to beat fast, became irregular, and caused seizures. Conclusion: In addition, unfiltered coffee can also trigger several things that can increase the risk of heart disease, because it increases homocysteine (a type of protein-forming amino acid) which is thought to be closely related to heart attacks, increased blood fat, and cholesterol.